COOPERATIVE LEARNING IN MATHEMATICS: A INTRA-CONTENTS STUDY - Pons, Rosa María; González-Herrero, María Elena; Serrano, José Manuel (Anales de Psicología / Annals of Psychology, 2008)
The present work studies the effects of a cooperative methodology in mathematics classes focusing on the interactions between processing and content. The authors start from the results obtained by other researchers that support the idea of cooperative learning methods been more effective in complex tasks, and focusing on a class of the 4th course of Compulsory Secondary Education (ESO), they develop the activities starting from a mix methodology (cooperative-individualistic), they divide academic content into three large-scale sections. The first block refers to the numerical operativity, the second segment is the one that belongs to algebra, and the third one corresponds to the contents that refer closely to the operational scheme (combinatory, probability, etc.). The results confirm that the dissimilarities in performance, however they are always in favour of cooperation, they are more noticeable in more innovative and complex contents, even though this contents